GÊNESE E REPRODUÇÃO DA CRENÇA NA EFICÁCIA DA POLÍTICA DE MICROCRÉDITO NO COMBATE À POBREZA - Bello Filho, Wilson de Barros (2010)
Why do people believe that microcredit is a public policy that helps to defeat poverty? That‟s the main question which is faced within this work. A preliminary research had suggested that neither evaluation studies nor a strongly developed conceptual framework existed, so that there were no easy explanations to that belief. In order to reveal the missed explanations, the analysis was structured in three moments: the historical and sociological backgrounds of microcredit policy, the analytical foundations of microcredit policy as a anti-poverty policy; the rhetorical tools used to strengthen the belief in microcredit policy. The study of historical and sociological backgrounds of microcredit policy made it possible to find that both political relations and political environment were necessary to its growth in popularity by the 1990 decade, when policies devoted to local scale begun to be accepted worldwide. The study of analytical foundations of microcredit policy confirmed that there is not a strongly developed conceptual framework and showed that there are many reasons to distrust the belief that microcredit policy is devoted to defeat poverty and is able to do it. The study of rhetorical tools used to communicate the strong belief in microcredit policy showed that these tools can compensate the analytical weakness of this belief. The use of rhetorical tools explains why people ignore all possible doubts upon microcredit policy and continue to believe it‟s a good way to defeat poverty.